0696 Memory Consolidation and Cerebral Oxygenation during Afternoon Naps in Older Adults with Amnestic Mild Cognitive Impairment. (27th April 2018) - Carlson, B W; Jones, K R; Craft, M A; Carlson, J R; Deardeuff, K; Tate, L R; Byerly, R; Ding, L; Yuan, H; Wenger, M; Hershey, L A
Abstract: Introduction: In amnestic mild cognitive impairment (aMCI), memory errors can occur when energy resources fail to match memory load, leading to disruptions in memory consolidation. This pilot study explored the relationship between memory load and consolidation to changes in cerebral oxygenation during afternoon naps in 11 persons (4 men, 58–76 years) with neurologist-verified aMCI. Methods: Studies were conducted on weekdays, between 2-4pm. Sixty-four channels of EEG and cerebral oximetry (measure of mixed venous cerebral oxygenation [rcSO2 ]) were recorded during a computer-based memory protocol and a 45-minute rest period. Test stimuli consisted of 36 pictures of common "to be remembered-TBR" objects (i.e. sweater) and its categorical cue (i.e. item of clothing). After presenting the TBR items, subjects recalled as many items as possible (free recall, -FR). If they missed >12 TBR objects, the missed objects are reshown with its corresponding categorical cue (cued recall-CR) and, the number correct recorded. Afterwards, the subjects were instructed to nap. The sum of remembered free and cued items (presleep FR+CR) mark the maximum possible items available for retrieval (memory load). The change [from pre- to post- nap] in FR and CR items determined levels of memory consolidation. Spearman rank correlations tested relationships between memory load-consolidation to change in rcSO2 during sleep. Results: After a nap, mean FR fell from 12.7 to 11.7; CR rose from 7.4 to 17.3 items. Time asleep ranged from 11.5–42.0 min (median: 27.2); the more time asleep, the more FR fell (r=-.74, p=.02). During sleep, rcSO2 fell by 2.5–2.9%; the higher prenap FR+CR, the lower the rcSO2 (rLeft =–.87, p=.002; rRight = -.93, p<.001). Decreases in left rcSO2 were associated with increases in FR (r=-.81, p=.008) and declines in CR (r=.85, p=.003). Conclusion: During sleep, declining rcSO2 may mark disruptions in memory consolidation and contribute to memory impairments in aMCI. Support (If Any): University of Oklahoma Vice President of Research Seed grants to BWC and MJW, and Pilot funding from the Oklahoma Center for Neuroscience to BWC and HY.